Geographical distribution of Archaeological places and how to develop them in Ranya district : a study in the geography of tourism (Raparin Journal of Humanities (RJH), 2023)
Archaeological sites are considered one of the main principles of tourism provision and an important human resource in this research entitled Geographical distribution of archaeological places and how to develop them in Ranya district (a study in the geography of tourism). The aim is to show how archaeological areas are distributed and developed in the study area, as well as to highlight the problems of archaeological areas. To achieve the goal of the study, descriptive and analytical methods were used, along with the use of geographic information systems (Arc GIS v. 10.8) to create maps related to the study area and the distribution of archaeological places in the district. The study has reached several results; there are about 63 archaeological sites in Ranya district that attract tourists. The geographical distribution of the archaeological places is so close to each other, which is important because tourists can visit several archaeological sites in a short time at a low cost. To develop the economy of the region and promote the tourism sector, there should be the construction of transportation roads to the archaeological areas in the district and further introduction and showing of the tourism potential in the study area.